Analysis of Tourist Motivation Factors in Choosing Adventure-Based Rafting Destinations in Sumedang - Rahesta Ardhya Pramesti; Rizal Ahmad Fauzi; Adang Sudrazat (Universitas Negeri Semarang, 2026)
Adventure-based tourism is growing rapidly as the preferences of tourists who are not only looking for entertainment, but also unique, challenging, and close to nature experiences. One form of adventure tourism that is in demand is rafting because it offers different sensations, challenges, and natural experiences. Sumedang Regency has great potential for the development of rafting tourism through supportive river conditions and beautiful natural panoramas. However, this potential has not been utilized optimally. This study aims to analyze the factors that influence tourists' decisions in choosing adventure-based rafting destinations in Sumedang Regency. The research uses a qualitative descriptive approach to gain an in-depth understanding of travelers' experiences, perceptions, and decision-making processes. Data was collected through in-depth interviews, observations, and documentation involving tourists, rafting managers, and tour guides with purposive sampling techniques. Data analysis was carried out using thematic coding and source triangulation to ensure the validity of the data. The results of the study show that tourists' decisions are influenced by two main dimensions, namely attraction and satisfaction. The attractiveness dimension includes accessibility, adventure experience, and digital promotion, while the satisfaction dimension includes amenities, price, quality of service, and security. The security factor is an important aspect in building tourist trust. In addition, digital marketing strategies and collaboration between tourism managers and local governments play an important role in increasing the competitiveness of destinations and tourist visits.